Question
upstudy study bank question image url

Write the quadratic function in the form \( y=a(x-h)^{2}+k \) and sketch its graph. \( y=x^{2}-4 x \)

Ask by Long Rojas. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The quadratic function \( y = x^{2} - 4x \) can be rewritten in vertex form as \( y = (x - 2)^{2} - 4 \). The graph is a parabola opening upwards with its vertex at (2, -4). It has x-intercepts at (0, 0) and (4, 0), and a y-intercept at (0, 0).

Solution

To convert y = x² - 4x into vertex form (y = a(x - h)² + k), follow these steps: 1. Start with the function:   y = x² - 4x 2. Factor out the coefficient of x² (in this case, it’s 1, so nothing changes):   y = x² - 4x 3. Complete the square:   • Take half the coefficient of x: ½(-4) = -2.   • Square it: (-2)² = 4.   • Add and subtract 4 inside the expression:     y = (x² - 4x + 4) - 4 4. Now write the quadratic as a perfect square:   y = (x - 2)² - 4 Thus, the vertex form is:   y = (x - 2)² - 4 Graph Details:  • Vertex: The vertex (h, k) is (2, -4).  • Axis of Symmetry: x = 2.  • x-intercepts: Set y = 0 in the original equation:   x² - 4x = 0 ⟹ x(x - 4) = 0 ⟹ x = 0 or x = 4.  • y-intercept: Set x = 0:   y = 0² - 4(0) = 0, so the point is (0, 0). Sketch Instructions:  1. Plot the vertex at (2, -4).  2. Draw the axis of symmetry, a vertical line through x = 2.  3. Mark the x-intercepts at (0, 0) and (4, 0) and the y-intercept at (0, 0).  4. Draw a smooth U-shaped (upward opening) curve passing through these points. This graph represents the parabola y = (x - 2)² - 4.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To rewrite the quadratic function \( y = x^2 - 4x \) in the form \( y = a(x-h)^2 + k \), we need to complete the square. 1. Start with \( y = x^2 - 4x \). 2. Take half of the coefficient of \( x \) (which is -4), square it, and add and subtract that value inside the function. Half of -4 is -2, and squaring it gives 4. 3. Rewrite the expression: \[ y = (x^2 - 4x + 4) - 4 = (x - 2)^2 - 4. \] So, in vertex form, this function is \( y = (x - 2)^2 - 4 \), where the vertex is \( (h, k) = (2, -4) \). Now sketching the graph: 1. The vertex is located at \( (2, -4) \). 2. The parabola opens upwards (since the coefficient of \( (x - 2)^2 \) is positive). 3. The axis of symmetry is the line \( x = 2 \). 4. For additional points, we can test \( x = 1 \) (which gives \( y = -3 \)), \( x = 3 \) (which also gives \( y = -3 \)), and \( x = 0 \) (which gives \( y = 4 \)). The graph looks like a 'U' shape opening upward with its vertex at \( (2, -4) \).

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy